Anticipating the effects of climate warming and natural habitat conversion on waterbird communities to address protection gaps. (March 2023) - Verniest, Fabien; Le Viol, Isabelle; Julliard, Romain; Dami, Laura; Guelmami, Anis; Suet, Marie; Abdou, Wed; Azafzaf, Hichem; Bendjedda, Nadjiba; Bino, Taulant; Borg, John J.; Božič, Luka; et al.
Abstract: Thermal adjustment of waterbird communities to climate warming is crucial but hampered by natural habitat conversion, increasing their climatic debt. As it is, in contrast, facilitated in protected areas, assessing the adequacy of the current protected areas network with respect to future climate and land-use changes and identifying priority sites to protect is of major importance. In this study, we assess the thermal adjustment limitations that non-breeding waterbird communities might experience by the end of the 21st century in the Mediterranean region to highlight priorities for wetland protection. Priorities were set by combining the exposure of waterbird communities to natural habitat conversion and climate warming with their thermal specialization. The latter was calculated using winter abundance data of 151 species from 2932 sites of the International Waterbird Census in 21 Mediterranean countries. Exposure was assessed using future projections of temperature and land-use under four CMIP6 scenarios (SSP1–2.6, SSP2–4.5, SSP3–7.0, and SSP5–8.5). We found that strictly protected areas are located in wetlands whose waterbird communities, without protection, would likely experience high limitations in thermal adjustment in the coming decades. This highlights that the location of existing protected areas may effectively support the thermal adjustment of waterbird communities to future climate warming. However, 490 sites considered at risk lack protection, including 32 sites of international importance for waterbirds, stressing the need to strengthen the protected areas network in these sites in priority. Our study provides important guidance for conservation planning in the Mediterranean region to support waterbird responses to climate change. Graphical abstract: Unlabelled Image